2023
DOI: 10.3389/fnmol.2023.1125934
|View full text |Cite
|
Sign up to set email alerts
|

1400 W, a selective inducible nitric oxide synthase inhibitor, mitigates early neuroinflammation and nitrooxidative stress in diisopropylfluorophosphate-induced short-term neurotoxicity rat model

Abstract: Organophosphate nerve agent (OPNA) exposure induces acute and long-term neurological deficits. OPNA exposure at sub-lethal concentrations induces irreversible inhibition of acetylcholinesterase and cholinergic toxidrome and develops status epilepticus (SE). Persistent seizures have been associated with increased production of ROS/RNS, neuroinflammation, and neurodegeneration. A total of 1400W is a novel small molecule, which irreversibly inhibits inducible nitric oxide synthase (iNOS) and has been shown to eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Our previous study demonstrated a significant increase in the inducible nitric oxide synthase (iNOS) in the brains of OPNA exposed adult rats, which persisted for long-term in glial cells [ 14 ]. Treatment with a highly selective iNOS inhibitor, 1400W hydrochloride, suppressed serum nitrite production and also reduced iNOS levels in the brain [ 14 , 15 ]. In addition, we found a significant increase in neuronal nitric oxide synthase (nNOS) post-SE, but unlike iNOS, it was only transiently upregulated [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated a significant increase in the inducible nitric oxide synthase (iNOS) in the brains of OPNA exposed adult rats, which persisted for long-term in glial cells [ 14 ]. Treatment with a highly selective iNOS inhibitor, 1400W hydrochloride, suppressed serum nitrite production and also reduced iNOS levels in the brain [ 14 , 15 ]. In addition, we found a significant increase in neuronal nitric oxide synthase (nNOS) post-SE, but unlike iNOS, it was only transiently upregulated [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both the 1400 W site and the tempol + 1400 W site were found to be greater than the tempol site for both the plateau and NO-dependent vasodilation. This was supported not only statistically but also based on the range of effect sizes of d = 1.03-1.22, indicating significant physiological differences in the effects of tempol compared to 1400 W. Mechanistically, it's possible 1400 W reduces oxidative stress, nitrosative stress, and/or proinflammatory cytokines while also directly suppressing the activity of iNOS (Massey et al, 2023;Méndez-Valdés et al, 2023;Putra et al, 2020;Tsai & Lein, 2021). Conversely, tempol may only be exerting an antioxidant effect with no direct action on iNOS.…”
Section: Non-hispanic Black Non-hispanic Whitementioning
confidence: 69%
“…Data from our lab, and others, have shown reduced cutaneous vascular responses to local heating in non-Hispanic Black young adults (Akins et al, 2022;Hurr et al, 2018;Kim et al, 2018;Kim & Brothers, 2020;Miller et al, 2021;Patik et al, 2018;Turner et al, 2020;Turner, Hayat, et al, 2023;Wolf et al, 2020;Wong et al, 2020). We recently demonstrated this reduction is due, in part, to activity of inducible NO synthase (iNOS), which is upregulated under stress conditions, such as increased levels of superoxide, and has been shown to contribute to reduced cutaneous NO-dependent vasodilation in hypertensive humans (Massey et al, 2023;Miller et al, 2021;Putra et al, 2020;Smith et al, 2011;Tsai & Lein, 2021). Previous data also indicates inhibition of superoxide and oxidative stress can improve NO-dependent vasodilation in non-Hispanic Black young adults (Hurr et al, 2018;Kim & Brothers, 2020;Patik et al, 2018;Turner, Hayat, et al, 2023;Wolf et al, 2020).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Our previous study demonstrated a signi cant increase in the inducible nitric oxide synthase (iNOS) in the brains of OPNA exposed adult rats, which persisted for long-term in glial cells [14]. Treatment with a highly selective iNOS inhibitor, 1400W hydrochloride, suppressed serum nitrite production and also reduced iNOS levels in the brain [14,15]. In addition, we found a signi cant increase in neuronal nitric oxide synthase (nNOS) post-SE, but unlike iNOS, it was only transiently upregulated [16,17].…”
Section: Introductionmentioning
confidence: 99%